PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA(STUDI PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020-2024) - Gusmiza Hadiya Putri; Dessi Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research sample is to determine the effect of ownership structure (institutional ownership, public ownership, managerial ownership) on dividend payment policies implemented by banks listed on the Indonesia Stock Exchange between 2020 and 2024. This study uses multiple linear regression analysis, with 15 banks distributing dividend information between 2020 and 2024. Data testing was processed using SPSS 22. The results of this study indicate: 1) Institutional ownership structure significantly influences Indonesian banking dividend policy between 2020 and 2024. 2) Public ownership structure significantly influences Indonesian banking dividend policy between 2020 and 2024. 3) Managerial ownership structure influences Indonesian banking dividend policy between 2020 and 2024. 4) Ownership structure (institutional ownership, public ownership, and managerial ownership) jointly influences Indonesian banking dividend policy between 2020 and 2024.